Elvis Costello, Joni Mitchell, and the torch song tradition - Smith, Larry David (Praeger, 2004)
Explores how the torch song tradition combined with the force of personality in two major singer-songwriters, examining their respective life's work and the ways in which they reflect the artists' similar and different outlooks on their world.